Communications networks - Kasera, Sumit; Narang, Nishit; Narang, Sumita (McGraw-Hill's AccessEngineering, 2005)
Communication Networks: Principles and Practice is a simple and jargon-free presentation on the core concepts of networking. The book adopts a novel approach, wherein each chapter first details a particular concept of networking and then explains it using.